Ternary Mixes of Self-Compacting Concrete with Fly Ash and Municipal Solid Waste Incinerator Bottom Ash - B. Simões; P. R. da Silva; R. V. Silva; Y. Avila; J. A. Forero (Applied Sciences, 2020)
This study aims to evaluate the potential of incorporating fly ash (FA) and municipal solid waste incinerator bottom ash (MIBA) as a partial substitute of cement in the production of self-compacting concrete mixes through an experimental campaign in which four replacement levels (i.e., 10% FA + 20% MIBA, 20% FA + 10% MIBA, 20% FA + 40% MIBA and 40% FA + 20% MIBA, apart from the reference concrete) were considered. Compressive and tensile strengths, Young’s modulus, ultra-sonic pulse velocity, shrinkage, water absorption by immersion, chloride diffusion coefficient and electrical resistivity were evaluated for all concrete mixes. The results showed a considerable decline in both mechanical and durability-related performances of self-compacting concrete with 60% of substitution by MIBA mainly due to the aluminium corrosion chemical reaction. However, workability properties were not significantly affected, exhibiting values similar to those of the control mix.